EDMODO: EXTENDING ENGLISH LEARNING BEYOND THE CLASSROOM - Wijayani, Pungky Wahyu; Weny, Eka Yanita (LUNAR, 2017)
The implementation of Kurikulum 2013 in Indonesia national education has created a great polemic among English teachers. The problem which most English teachers face is the limited face-to-face teaching periods. The English subject in SMAs now is only taught in one meeting per week. This few in-class teaching session is considered to be insufficient for addressing students’ needs to master English. In digital era, bringing digital flipped classroom into ELT will be a good solution not only for students but also for teachers to increase the English teaching and learning experience. Here, we would like to introduce Edmodo as an online website for learning which can be used in flipped classrooms. Edmodo offers various online applications in the form of website that has unique and interesting features for teachers to use in English classes. By integrating Edmodo into their teaching process, teachers are expected to extend the English teaching beyond the classroom. Teachers will be able to tackle the problem in terms of decreasing in-class time to build students’ English proficiency. In this paper, we would like to discuss more the implementation, features and strength of Edmodo in teaching English.